Digital business security development [ management technologies - Bryant, Kay , 1954-; Gammack, John G.; Kerr, Don , 1952- (Gale virtual reference library, 2011)
"This book provides comprehensive coverage of issues associated with maintaining business protection in digital environments, containing base level knowledge for managers who are not specialists in the field as well as advanced undergraduate and postgraduate students undertaking research and further study"-- Provided by publisher